PENINGKATAN HASIL BELAJAR BAHASA INDONESIA MELALUI PERMAINAN DADU EDUKATIF DI KELAS 5B SD MATREYAWIRA - Riani, Rina; Amizera, Susy; Juliana S, Juliana S (Universitas Tanjungpura, 2025)
Indonesian language plays a crucial role asthe foundation for scientific and social communication within the educational setting. However,the learning outcomes of grade 5B students at SD Maitreyawira Palembang had yet to reach the expected standards. This issue stemmed from the continued use of conventional teaching methods, which were perceived as monotonous and unengaging. Initial observations indicated that only 68% of students achieved learning mastery, falling short of the established Minimum Competency Criteria (KKM) of 85%. To address this challenge, the researcher conducted Classroom Action Research (CAR) by implementing an educational dice game as an interactive learning medium. The study was conducted over two cycles, each comprising four phases: planning, action, observation, and reflection. A total of 25 students participated in the study, consisting of 12 boys and 13 girls. Data were collected through field notes, observation checklists, and learning outcome assessments. The findings revealed a notable improvement in student performance, with the mastery level rising to 76% in the first cycle and reaching 88% in the second cycle surpassing the KKM threshold. Furthermore, students demonstrated increased motivation and active participation during lessons. The use of educational dice games effectively fostered an enjoyable classroom environment, enhanced material comprehension, and promoted collaborative learning. Therefore, educational dice games can be considered a practical and engaging strategy to enhance Indonesian language learning outcomes at the elementary level.